Desarrollo del lenguaje en educación inicial - Bautista Basantes, Jessica Lucero (2017)
This research has like aim analyses the children language development of initial edu-cation “Isidro Ayora" The aim is focused to diagnose children language development advance in initial education. In that way, the information was obtained about the dif-ferent methodological strategies, take in account the some aspects like: stories, rhymes, songs and words repetitions that is use to strengthening the language in learners since first year of education, giving teachers and parents the opportunity to have new procedures that will help students to develop easily within the educational process. The mythology that was used for the research was the qualitative and quanti-tative and for the collect the data was used the survey technique applied to teachers, the interview for the psychologists and the observation for children of initial educa-tion. Accomplishing to determinate that exist a limited participation in the activities students that permit the fluid language development. After researching and know the different authors' theories, it conclude that humans have an innate ability to learn lan-guage but development and training about this one, it only will be possible if a envi-ronment society exist around the child and a suitable stimulation that provides the appropriate linguistic use….